Informiranje bolnika z rakom kot element celovitega upravljanja kakovosti - Skela-Savič, Brigita (Obzornik zdravstvene nege, 2003)
Informing a patient is a complex; besides information from the doctor about the disease and its treatment and from the nurse about nursing care, the patient needs many other informations to understand the process of treatment, side effects and related measures, all of which facilitates hospital stay and enhance the quality of life in the time of treatment. The measurement of patient satisfaction should aim at a comprehensive evaluation of the situationand serve as the preparative phase for the project of improvements, their realization and evaluation. Attendance to patient satisfaction helps health management to ascertain learning needs of the employees, to discover areas where organizational problems occur and to find out about eventual flawsin the health care of patients and in recompensation and moral enhancement of the employees. Certain improvements were introduced in the Institute of Oncology in Ljubljana in the last five years period. Our goal in it was to improve patient satisfaction in the area of information, communication and education.
Keywords: ankete; Bolnik, pravice; bolniki; Health Education; Informed Consent; informiranje; Kakovost zdravstvenega varstva; Neoplasms; Novotvorbe; Patient Advocacy; Quality Of Health Care; Questionnaires; rak (medicina); tumor; Zavestna privolitev; Zdravstvena vzgoja